STUDENTS' PERCEPTIONS TOWARD VIDEOS AS MEDIA OF LISTENING LEARNING - Miranda Halomoan; Fauzi Miftakh; Yousef Bani Ahmad (IKIP Siliwangi, 2022)
The development of technology is helping humans in many sectors including education. Learning English is very important because English is an international language. Moreover, to be able to speak English, students must master 4 skills in English, namely listening, speaking, reading, and writing. Students consider listening learning by using audio as the method is not interesting. Listening learning by using english videos is helping students learn interestingly. In this study, the author did a research about students' perception towards english videos as listening learning media. The participants of this research were 2 senior high school students in Jakarta. The qualitative method in this research is based on Creswell. The result of this study is the positive perception of students towards english videos as listening learning method. Keywords: Videos, Listening, Students’ Perceptions